Fasting plasma mannose levels are associated with insulin sensitivity independent of BMI in Japanese individuals with diabetes - Amano, Eri (Diabetol Metab Syndr, 2018)
BACKGROUND: Recently, an integrated network analysis has revealed dysregulation in the metabolism of mannose, a glucose epimer, in severely obese individuals without diabetes. In addition, fasting plasma mannose levels (M(0)) are associated with insulin resistance independent of BMI. Since the association between mannose and insulin sensitivity (IS) in those with impaired glucose tolerance remains unknown, we aimed to investigate this association in individuals without severe obesity but with varying degrees of glucose tolerance. METHODS: Based on 75 g OGTT data in Japanese individuals without diabetic medication, individuals were classified as having normal glucose tolerance (NGT), impaired glucose metabolism (IGM), or diabetes (DM). In each group, 25 individuals were consecutively recruited [total 75 individuals, age: 65 ± 11 (mean ± SD); BMI: 24.9 ± 3.8 kg/m(2)]. QUICKI and Matsuda index (MI) were calculated as IS indices. M(0) was assayed using HPLC. Normally-distributed log(e)-transformed (ln-) values were used for MI and leptin. RESULTS: In the simple regression analysis, ln-MI was negatively correlated with BMI (NGT: r = − 0.639, IGM: r = − 0.466, DM: r = − 0.613) and ln-leptin (NGT: r = − 0.480, IGT: r = − 0.447, DM: r = − 0.593) in all 3 groups. Ln-MI was not significantly correlated with M(0) in NGT (r = 0.241, P = 0.245) and IGT (r = − 0.296, P = 0.152) groups, it was moderately and negatively correlated in the DM group (r = − 0.626, P < 0.001). Similar results were obtained, when QUICKI was used instead of MI as an index of IS. In multiple regression analysis in the DM group, QUICKI (Q) and ln-MI (M) were independently predicted by BMI (Q: β = − 0.413; M: β = − 0.400) and M(0) (Q: β = − 0.413, M: β = − 0.426), accounting for 51.2% (P = 0.0004) and 51.2% (P = 0.0004) of the variability, respectively, which was larger than the prediction for BMI alone (Q: 38.4%, M: 37.6%). CONCLUSION: Fasting plasma mannose was associated with IS independent of BMI in Japanese individuals with DM.